Gender and innovation in the new economy : women, identity, and creative work - Poutanen, Seppo; Kovalainen, Anne (Palgrave Macmillan, 2017)
This book provides a thorough and novel examination of the gendered nature of innovations in the new economy. It tracks the contemporary shift from heavy industry to game industry and how this has altered relationships between gender, identity, corporate culture, creative work, and the future of business. Through empirical research and theoretical analysis, the authors present their own carefully contextualized cases and conceptual frameworks relating themes of innovation and gender to recent theories concerning globalization and transnationalism. This wide-ranging and interdisciplinary text provides readers with insightful entries on what innovations are and the ways innovation processes become gendered. It explores the business landscape based on creative work and offers a wealth of information for scholars of entrepreneurship, management, sociology, cultural studies, and communication.- Resumé vydavatel
Keywords: inovace; gender; podnikání; innovations; business; elektronické knihy; monografie; electronic books; monographs